Lumpy investment, lumpy inventories - BACHMANN, Ruediger (Institutional Knowledge at Singapore Management University, 2016)
The link between the microenvironment (frictions and heterogeneity) and the macroeconomic dynamics of general equilibrium macromodels is influenced by exactly how general equilibrium closes the model. We make this observation concrete using the recent literature on how nonconvex capital adjustment costs influence aggregate investment dynamics. We introduce inventories into a two-sector lumpy investment model and find that nonconvex capital adjustment costs dampen and propagate investment impulse responses, more so than without inventories. With two means of transferring consumption into the future, fixed capital and inventories, the tight link between aggregate saving and fixed capital investment is broken.